Can you know me better? An exploratory study combining behavioural and physiological measurements for an objective assessment of sensory responsiveness in a child with profound intellectual and multiple disabilities - Lima, M.; Silva, K.; Magalhães, A.; Pestana, M.H.; Sousa , L. (Journal of Applied Research in Intellectual Disabilities, 2012)
Sensory assessment of individuals with profound intellectual and multiple disabilities (PIMD) can be extremely difficult for several reasons, including the idiosyncratic reactions that these individuals commonly exhibit to environmental stimuli. This case report presents a combination of behavioural and physiological measurements aimed at providing an objective assessment of the sensory responsiveness of a child with PIMD. Settings/location, subjects, and interventions: The participant was presented, at his home, with a set of stimuli commonly used during sensory interventions. Responsiveness to these stimuli was assessed in terms of motor movements, heart rate and electrodermal responses. Treatment outcomes: Although the child only seemed to react to two of the presented items, interesting connections were observed between his motor and physiological responsiveness. Conclusions: The methodological approach here presented appears to constitute a useful resource for understanding and ascribing meaning to the behaviours of children with PIMD that represent specific reactions to particular stimuli. With such a resource,